STEM Learning to Stimulate Learners' Science Process Skills on Food Digestion System Material - Darlis Ab (Science Center Group, 2024)
Background: STEM (Science, Technology, Engineering, and Mathematics) education has emerged as a strategic approach to preparing students for twenty-first-century challenges by fostering critical thinking, problem-solving, and scientific inquiry skills. In science learning, particularly on complex biological topics such as the human digestive system, the development of science process skills remains essential yet insufficiently stimulated through conventional instruction. Objective: This study aimed to analyze the effectiveness of STEM-based learning in stimulating students’ science process skills on the topic of the food digestion system. Methods: A quantitative quasi-experimental design with a non-equivalent control group was employed. Participants were secondary school students selected through purposive sampling and assigned to an experimental group receiving STEM-based instruction and a control group receiving conventional teaching. Science process skills—comprising observation, measurement, data analysis, and evaluation—were assessed using validated pre- and post-tests. Additional data were collected through observation sheets and student reflective journals. Data were analyzed using independent samples t-tests to determine differences between groups. Results: The findings indicated a statistically significant improvement in science process skills among students exposed to STEM-based learning compared to those in the control group (p < 0.05). The experimental group demonstrated greater gains in observational accuracy, analytical reasoning, and evaluative skills. Enhanced student engagement, collaborative interaction, and conceptual understanding were observed during STEM activities supported by digital media and simulations. Conclusion: STEM-based learning effectively stimulates science process skills in learning the food digestion system. The integration of interdisciplinary inquiry, hands-on experimentation, and technological support fosters meaningful engagement and higher-order scientific thinking. These findings support the broader implementation of STEM approaches in secondary science education.